2014
DOI: 10.1111/liv.12623
|View full text |Cite
|
Sign up to set email alerts
|

New reliability criteria for transient elastography increase the number of accurate measurements for screening of cirrhosis and portal hypertension

Abstract: New reliability criteria for TE measurements increase the number of patients with accurate measurements without affecting diagnostic performance for detecting cirrhosis and portal hypertension. Aetiology of liver disease and aminotransferases should be considered when assessing liver fibrosis by TE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 61 publications
2
99
0
Order By: Relevance
“…[24][25][26] All relevant confounding factors for the TE-based assessment of liver fibrosis induce false-high liver stiffness results leading to an overestimation of liver fibrosis stage. 27 Thus, they cannot explain the very low prevalence of liver fibrosis !F3 observed in our study. Since sample size limits the conclusions of our study, collaborative efforts are required to perform large international studies.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] All relevant confounding factors for the TE-based assessment of liver fibrosis induce false-high liver stiffness results leading to an overestimation of liver fibrosis stage. 27 Thus, they cannot explain the very low prevalence of liver fibrosis !F3 observed in our study. Since sample size limits the conclusions of our study, collaborative efforts are required to perform large international studies.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were infected with HCVsubtype 1a and had the IL28B C/T genotype. [19]. Advanced liver fibrosis and cirrhosis were defined by liver stiffness values > 9.5 kPa and > 12.5 kPa, respectively [20].…”
Section: Characteristics Of Patients With Boc Add-onmentioning
confidence: 99%
“…TE has been validated in different liver diseases and has been shown to be accurate in diagnosing fibrosis in the F3-F4 stages with a specificity of 72 % and sensitivity of 86 % [5]. Previous studies have demonstrated that the patient's anthropometric characteristics and etiology of liver disease are factors that can influence the reliability of TE measurements and that these factors may influence the diagnosis of liver fibrosis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%